Using distance learning strategy in students’ acquisition of conceptual and procedural knowledge in mathematics - ghunaimat, mohammad Ali (Department of Mathematics Education University of Muhammadiyah Malang, 2024)
The study investigates the effect of using Distance learning (DL) on students’ acquisition of conceptual and procedural knowledge in mathematics. The study used the quasi-experimental approach, where the study was applied by two groups of ninth grade students (experimental, 25 students, and control, 26 students), the experimental group was taught by using Distance learning, and the control group was taught in the usual way, after verifying the validity coefficients. And reliability for testing conceptual and procedural knowledge. The results demonstrated statistically significant differences favoring the experimental group, suggesting that Distance learning has a beneficial impact on mathematics instruction. The study included recommendations on the necessity of promoting Distance learning usage among students and teachers additionally the function of educational technology in the process of teaching and learning mathematics.